Transparansi, Pengawasan, Akuntabilitas, Redesain Sistem Penganggaran dan Kinerja Badan Layanan Umum - Frisiska Oktarina; Yulia Saftiana; Azwardi Azwardi (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to determine and analyze the effect of transparency, oversight, accountability and redesign of the budgeting system either partially or simultaneously on the performance of Public Service Agencies. The population was taken from PPSPM, PPK, Planning/Budget Coordinator, Finance, Academic Section along with Staff and SPI so that the population was 204 people. The sampling technique used is saturated sampling so that the entire population of 204 people is taken as a sample. The analysis technique used is multiple regression with the help of the SPSS application by testing the hypothesis using the t test and F test. The partial results show that the transparency variable has no significant effect on financial performance with a significance value of 0.552. The monitoring variable has a significant effect on financial performance with a significance value of 0.008. The accountability variable has no significant effect on financial performance with a significance value of 0.738. The redesign variable of the budgeting system has a significant effect on financial performance with a significance value of 0.024. Simultaneously the variables of transparency, supervision, accountability and redesign of the budgeting system simultaneously have a significant effect on financial performance with a significance value of 0.000. The conclusion shows that partially only the monitoring and budgeting system redesign variables have an effect on financial performance while simultaneously all independent variables including transparency, supervision, accountability and budgeting system redesign simultaneously have a significant effect on financial performance.